(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aimed to determine the anxiety and fatigue levels of athletes preparing for the 2025 Central Sulawesi Pre-National Games before competition. Volleyball Anxiety and fatigue are important psychological and physiological factors that can influence athlete performance, concentration, emotional stability, and physical readiness during competitive situations. High levels of anxiety and excessive fatigue may reduce athlete confidence, decision-making ability, and overall performance during matches. Therefore, identifying athlete psychological and physical conditions before competition is essential for optimizing training and recovery programs. This research employed a survey method using a quantitative descriptive approach. Data collection was conducted through questionnaires distributed to athletes preparing for the 2025 Central Sulawesi Pre-National Games. The sample consisted of 12 volleyball athletes selected using a total sampling technique. The instruments used in this study included validated anxiety and fatigue questionnaires. Data analysis was performed using descriptive statistical techniques, including mean, standard deviation, percentage distribution, and categorization analysis. The findings revealed that the average anxiety score of the athletes was 65.17. Based on the categorization results, 16.67% (2 athletes) were classified as having low anxiety, 58.33% (7 athletes) experienced moderate anxiety, and 25.00% (3 athletes) demonstrated high anxiety levels. Regarding fatigue, 41.67% (5 athletes) were categorized as experiencing light fatigue, while 58.33% (7 athletes) experienced moderate fatigue. No athletes were classified in the heavy fatigue category. These findings indicate that the anxiety and fatigue levels of the 2025 Central Sulawesi PRAPOPNAS volleyball athletes were generally within the moderate category. Therefore, mental training, recovery management, and psychological monitoring are recommended to optimize athlete readiness before competition.